Highly integrated sensors based on microstructured optical fibers - Zheng, Yu (Nanyang Technological University, 2020)
Microstructured optical fibers (MOFs) have been widely studied in terms of the fabrications, properties and applications in the past few years, since a silica fiber with a complex holey cladding structure was firstly fabricated in 1996. Due to the inherent properties such as immunity to electromagnetic interference, light weight, versatile designs and diverse optical and mechanical performances, MOFs possess an enormous potential in the field of sensing applications. In this thesis, we investigate several approaches to improve the performance of fiber sensors based on the proper design and fabrication of MOFs and post-processing techniques. Firstly, we design and fabricate a novel hollow core microstructured optical fiber (HCMOF) by stack-and-draw process. The HCMOF consists of a large hollow core surrounded by twelve crown-like air holes. Due to the special structure, the HCMOF allows the multiple-mode propagation in the hollow fiber core. In addition, it is easy to obtain a robust integration with single mode fibers (SMFs) since the diameter of the fiber and the thickness of the silica cladding are around 125 µm and 30 µm, respectively. Secondly, we develop an in-line Mach–Zehnder interferometer (MZI) sensor for bending measurement based on the specially designed HCMOF. Optical fiber bending sensors have been broadly applied in the fields of mechanical engineering and health monitoring. Among all specifications of fiber bending sensors, bending sensitivity is a critical performance indicator. Hence, we theoretically and experimentally investigate the relationship between the bending sensitivity and the hollow core size, and prove that the bending sensitivity is positively dependent on the hollow core size. Specifically, the bending sensitivity of our sensor at small bending angle is improved 10 times by increasing the hollow core size compared with the sensor consisting of a small-size hollow core. Thirdly, we explore a method to enhance the strain sensitivity of the in-line MZI sensor by fabricating periodical structures on the specially designed HCMOF. Introducing periodical structures via electric arc discharge alters the power ratio of guided modes in the hollow core. External tension is further to change the power ratio of guided modes, which leads to the variation of the extinction ratio in the transmission spectrum. Fourthly, the performance of optical fiber sensors is generally limited by either their dynamic range or resolution, which is a trade-off existing in almost all kinds of sensors. We theoretically and experimentally demonstrate a multimode interferometer sensor based on a suspended core microstructured optical fiber (SCMOF) to improve the dynamic range and resolution simultaneously. The multimode interferometer sensor is fabricated only by splicing a section of SCMOF between two segments of SMFs with central alignment. The transmission spectrum of the SMF–SCMOF–SMF structure features dense fringes modulated by a lower envelope, which is induced by the multimode interference. Strain sensing is applied to validate the characteristics of the sensor.